Analysis of the impact of changes in the 11% VAT rate in increasing tax revenue - Safitri, Erdila Yuni; Nataliawati, Rita; Qosim, Qosim; Winarsih, Tri (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2024)
This research aims to determine the impact of changes in value added tax rates in terms of increasing tax revenues at the Lamongan Pratama Tax Service Office. This research was carried out at the Laamongan Pratama Tax Service Office. The method in this research uses qualitative methods. This research uses primary and secondary data sources obtained through documentation, observation and interviews. Data analysis uses data reduction. Meanwhile, to validate the data using triangulation techniques of source, time and technique. Research results (1) The implementation of changes to the 11% VAT rate at KPP Pratama Lamongan has been good and effective, (2) The value added tax rate of 11% has also been implemented thoroughly so that the realization of tax revenues at the Pratama Lamongan tax service office has increased from the previous year (3) The impact of the change in the value added tax rate of 11% at the Pratama Lamongan tax service office is in the form of increasing tax revenue